Etika, Etos Kerja dan Sikap Professional dalam Bisnis - Subroto, Setyowati (PERMANA, 2013)
In carrying outactivitiesin various fields, especially in the business world, ethics, work ethic and professional attitude is a series that can not be separated from one another. Therefore, abusiness must be ableto beprofessional, to understand the principles ofethicsand always have awork ethic. Keywords: Ethics, Work Ethics and Professional Attitude